Potential Applications and Active Substances of Lavender Essential Oil as An Anti-Hypertension: Narrative Literature Review - Setyawan, Aris; Kintoko, Kintoko (Indonesian Journal of Global Health Research, 2024)
Hypertension is one of the Cardiovascular Diseases (CVD) which is the highest cause of death, and current treatment has many side effects that can be life-threatening, so researchers are interested in providing safe treatment solutions. One of them is traditional medicine such as aromatherapy. Therefore, it is necessary to carry out narrative research in the literature reviewing the effectiveness of lavender aroma therapy in reducing blood pressure in hypertensive patients. This research uses a Narrative Review study approach which focuses on evaluating several previous research results related to the topic. Based on data used by Google Scholar, Pubmed, and Spinger between 2019 and 2024. A total of 1,394 articles were found in the initial search stage, after filtering based on title, keywords and abstract this was reduced to 10 articles. And finally only 4 articles were selected that fit the criteria. There were 2 types of lavender aromatherapy applications, namely topical and inhalation. As well as two anti-hypertension active substances, namely linalool and linalool acetate. Lavender aromatherapy is effective in lowering blood pressure in hypertensive patients. The mechanism of reduction can be explained by the active anti-hypertensive substance (linalool & linalool acetate) and its application (inhalation & topical). However, further research with better designs is still needed.